Some Parallels Between Cumulative Tales and Ritual Songs - Vardanyan, Nvard (Bulletin of Yerevan University B: Philology, 2023)
Cumulative or chain tales are among the least studied types of Armenian folklore. As a subgenre of fairy tales, cumulative tales stand out not so much in content as in structural features of the narrative. The initial structure is a structure accumulating with certain stable repetitions, which includes a new component at each cycle of the plot. A similar cumulative structure is also characteristic of the composition of some folk ritual songs, where the repetition of motives suggests a genealogical commonality of plots.The article examines a number of cumulative texts of fairy tales and songs using the intertextual method. In the sdudied material we also included highly artistic adaptations of cumulative plots by Hovhannes Tumanyan, examining them among the folklore versions and other examples of ritual folklore. The article studies the principle of the development of a cumulative chain with successive links of birth and death, creation and decay, the principle of the formation of a chain based on the logic of the life cycle, which is also the main idea of New Year and wedding ritual folklore. This is what determines the genealogical commonality of cumulative tales with New Year and wedding ritual texts and reveals the abundance of motifs associated with the bride, groom and wedding in the cumulative structures under consideration.
Keywords: cumulative tale; ritual song; “Here it is”; “Come and see”; “Sparrow”; “Tailless Fox”; “Fairy tale, this is my grandfather”; chain structure; creation; destruction; bride and groom